Szkoły Promujące Zdrowie. Przesłanki i założenia teoretyczne dla działalności praktycznej - Herman, Tomasz (Kultura-Społeczeństwo-Edukacja, 2014)
In this article author will approximate the concept, history and organization of the health promoting school. Successively the key concepts for this model: health, health behaviors, lifestyle health promotion, health education and prevention will be discussed. The author shows how much importance they have for the practical dimension of this project’s rationale and theoretical assumptions.